The Dialectic of Duration - Bachelard, Gaston 1884-1962; McAllester Jones, Mary; Chimisso, Cristina (Manchester Clinamen, 2000)
Gaston Bachelard (1884 -1962) is one of the most famous philosophers of the French 20th century, leaving a huge body of writing stretching from his first publication in 1928 right up to the time of his death. His subject matter was diverse - to date, the texts chosen for translation into English have reflected his 'literary critical' writing career, but there remains an impressive body of untranslated work on the philosophy of science. He held the chair of History of Philosophy of Science at La Sorbonne.Bachelard's work has and retains a profound influence in the French-speaking world. His writing career as a whole can be understood as a meditation on science in the context of human being and the creative, 'poetic' side of human nature, featuring restless reformulations of psychoanalysis and phenomenology .'Dialectic of Duration' addresses the nature of time, taking issue specifically with Henri Bergson's notion of duration, or 'lived' time, as found in Bergson's 'Duration and Simultaneity' and 'Matter and Memory'. For Bachelard, contra Bergson, the experience of lived time was fractured, interrupted, not 'single' and continuous; he argues that there is no one underlying thread - that time is multiple and discrete. This had and has crucial significance for the debate between Bergson and the physics of Relativity.This first time English translation has been undertaken by Bachelard scholar Dr Mary McAllester Jones of Strathclyde University, whose 'Gaston Bachelard - Subversive Humanist' has done much to broaden Bachelard's English-language reputation. The introduction is by Dr Cristina Chimisso.
Originally published in 1936, revised 1950
Keywords: Philosophy